Cannabidiol for treatment of irritability and aggressive behavior in children and adolescents with autism spectrum disorder: background and methods of the cannabidiol study in children with autism spectrum disorder study - Sannar, Elise M.; Winter, Joan; Franke, Ronda K.; Werner, Emily; Rochowiak, Rebecca; Romani, Patrick W.; Miller, Owen S.; Semmler, Nicole; Bainbridge, Jacquelyn L.; Natvig, Crystal; Mikluich-Gilbertson, Susan K.; Tartaglia, Nicole R. (International Journal of Clinical Trials, 2025)
Background: Autism spectrum disorder (ASD) is a neurodevelopmental disorder commonly associated with behavioral challenges. There are few evidence based pharmacological interventions available for the treatment of behavioral symptoms associated with ASD. Cannabidiol (CBD), the non-intoxicating component of cannabis, has known neuroprotective, antiepileptic, anxiolytic, and antipsychotic effects and may be useful in treating the behavioral symptoms of ASD. Methods: We describe the research methods of a 27-week randomized placebo-controlled crossover trial to evaluate the safety and efficacy of oral CBD for the treatment of irritability and aggression associated with ASD, as measured by the irritability subscale of the aberrant behavior checklist-2nd edition (ABC-2) in children and adolescents. Conclusions: There is significant need for clinical research exploring alternative medications for the treatment of behavioral symptoms of ASD. Upcoming results from this trial will help answer the question of whether CBD may be a useful intervention in the management of ASD. Clinical trial registry: NCT04520685.